The MEDIATING ROLE OF KNOWLEDGE SHARING ON WELLBEING AND PERFORMANCE: EVIDENCE FROM BANKING EMPLOYEES IN JAKARTA - Ahmad Firdaus; Oceano Fauzan, Muhamamd (Management Department, Faculty of Economics and Business, Universitas Jambi, 2026)
While employee wellbeing is recognized as a crucial element in the workplace, the psychological mechanism, particularly the mediating role of knowledge sharing, that links it to employee performance remains underexplored. This study aims to examine the effect of employee wellbeing on performance, with knowledge sharing as a mediating variable. A quantitative approach was employed by distributing structured questionnaires to 217 banking employees in Jakarta. The data were analyzed using Structural Equation Modeling. The results indicate that employee wellbeing and knowledge sharing have a positive and significant direct effect on employee performance. Furthermore, the Sobel test confirms that knowledge sharing significantly mediates the relationship between employee wellbeing and employee performance. These findings demonstrate that wellbeing does not automatically translate into high performance solely through individual effort, but rather operates through a social mechanism where positive psychological conditions drive knowledge exchange.